2014
DOI: 10.1007/s10482-014-0255-8
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of Aspergillus oryzae NRRL 3484 by mutagenesis and optimization of culture conditions in solid-state fermentation for the hyper-production of extracellular cellulase

Abstract: Spore suspensions of Aspergillus oryzae NRRL 3484 were subjected to mutagenesis using ultraviolet-irradiation followed by chemical treatments to improve the biosynthesis of cellulase. Ten mutant strains namely UEAC7, UEAR5, UNAC4, UNAC16, UNAR19, UNBC7, UNBR3, UNBR10, UNBR23 and UNBR25 were selected and their extracellular cellulase activities were assayed. Mutant UNAC4 gave the highest cellulase production [2,455 ± 28 U/g-dry substrate (ds) for filter paper-ase (FP-ase)] in a yield 4-fold exceeding that of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
3
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 63 publications
0
7
0
1
Order By: Relevance
“…The highest level of β‐glucosidase activity determined in the SSAO koji was 35.32 U g −1 recorded at 36 h during the koji‐making process, a level similar to that reported by El‐Ghonemy et al . (), of 35 ± 0.2 U g −1 for UNBR25 (the mutant form of A. oryzae NRRL 3484). In contrast, the maximum β‐glucosidase activity in the SSAON koji appeared after 40 h koji fermentation, and was 107% higher than the equivalent level in the SSAO koji ( P < 0.05).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The highest level of β‐glucosidase activity determined in the SSAO koji was 35.32 U g −1 recorded at 36 h during the koji‐making process, a level similar to that reported by El‐Ghonemy et al . (), of 35 ± 0.2 U g −1 for UNBR25 (the mutant form of A. oryzae NRRL 3484). In contrast, the maximum β‐glucosidase activity in the SSAON koji appeared after 40 h koji fermentation, and was 107% higher than the equivalent level in the SSAO koji ( P < 0.05).…”
Section: Resultsmentioning
confidence: 99%
“…Beta‐glucosidase activity was determined using p‐nitrophenol‐β‐D‐glucopyranoside (pNPG), according to the methods of El‐Ghonemy et al . (). Briefly, a 2‐mL reaction mixture containing 0.1 mL of enzyme extract, 0.9 mL of pNPG solution (5 m m ) as the substrate, and 1 mL of sodium acetate buffer (50 m m , pH 4.8) was incubated at 50 °C for 10 min.…”
Section: Methodsmentioning
confidence: 97%
“…Aspergillus oryzae, as a Generally Recognized as Safe microbe, has been widely utilized in traditional food processing for centuries [2]. Known for its secretion of ligninolytic and hydrolytic enzymes [3], this filamentous fungus strain has been used to produce biodiesel, lipids and enzymes directly from lignocellulosic feed stocks [4][5][6]. The hydrolysates of the lignocellulose contain a mixture of glucose and xylose, [7] although the poor utilization of xylose remains the dominant hurdle to overcome with this organism [8].…”
Section: Introductionmentioning
confidence: 99%
“…Endoglucanases are the largest groups of enzymes constituting third group of enzyme world-wide and used commercially for more than 30 years [9]. Cellulases are used in various industrial applications such as alcohol production, fruits and vegetables extraction, brewing and malting [10], animal feed, food, paper and pulp, textile and laundry industries, agriculture and even for academic and research purposes [11]. The demand for cellulases is increasing day by day due to its applications in production of second generation biofuels and previous studies have reported that about 20% of world enzyme market was constituted by cellulolytic enzymes [12].…”
Section: Introductionmentioning
confidence: 99%